Efficiency of apple juice clarification with using of nano-sized mineral oxides - Sachko, Anastasiia; Kobasa, Igor; Moysyura, O.; Vorobets, Mariia (My University, 2020)
Introduction. The aim of presented work was the investigation of the efficiency of clarification of direct pressing apple juice with utilization of nano-sized powders of both silicon dioxide and titanium dioxide, modified silicon dioxide powder in comparison with bentonite clay. Materials and methods. The juice used for laboratory testing was squeezed from "Glory to the Winners" apples. Modified silicon dioxide powder (AMD-2, specific surface area 280 m2 /g) and nano dispersed powders of both silicon dioxide (specific surface area 300 m2 /g) and titanium dioxide (specific surface area 50 m2 /g) were selected as clarifiers. For comparison, we used bentonite clay (specific surface area 160 m2 /g). The optical density was measured with spectrophotometr, the content of dry substances was evaluated refractometrically, pH and titratable acidity was determined according to known methods. Results and discussion. Prospects of mineral oxides of titanium and silicon utilization for clarification of apple juice have been shown. It was established that the most effective clarifiers were SiO2 powder and suspension. Optimal weight of SiO2 is 2.5 g per 1 liter of juice; steep time is not more than 24 hours. The form (in powder or suspension) has no significant effect on the result of clarification. The worst clarification ability bentonite clay demonstrated. It was confirmed that utilization bentonite in suspension form increases the clarification efficiency. Growth a mass of bentonite from 0.1 to 2.5 g per l of juice impairs its optical properties. The effect of temperature of clarification processes on its efficiency and influence of the “juice-clarifier” contact time on the physical-chemical properties of the finished product were investigated. It was shown that the result of clarification is better at low temperature (4 ºС), and all the used oxides are able to slow down the flow of natural processes of fermentation of raw apple materials. It was found that more than 24 hours contact of juice with clarifiers has a negative influence on the clarification result for all tested samples. Conclusion. Nano-dispersed oxides of titanium (IV) and silicon (IV) could be effectively utilized to clarify of fresh direct pressing apple juice. Their clarifying ability is higher than bentonite clay and they could be brought in juice without pre-treatment, in the form of powder.
Efficiency of apple juice clarification with using of nano-sized mineral oxides
Keywords: Clarification; Apple juice; Titanium dioxide; Silicon dioxide; Bentonite